2001
DOI: 10.1046/j.1365-2389.2001.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Vents and seals in non‐steady‐state chambers used for measuring gas exchange between soil and the atmosphere

Abstract: Summary Despite decades of research to define optimal chamber design and deployment protocol for measuring gas exchange between the Earth's surface and the atmosphere, controversy still surrounds the procedures for applying this method. Using a numerical simulation model we demonstrated that (i) all non‐steady‐state chambers should include a properly sized and properly located vent tube; (ii) even seemingly trivial leakiness of the seals between elements of a multiple‐component chamber results in significant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
176
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(180 citation statements)
references
References 20 publications
2
176
0
2
Order By: Relevance
“…The NE ff was calculated using the exponential change in chamber headspace CO 2 concentration (Kutzbach et al, 2007) regressed with time, as a function of volume, pressure and air temperature inside the chamber, according to the ideal gas law. The exponential regression was applied following because covering the soil and vegetation can manipulate the sponta-neous CO 2 fluxes across the soil-vegetation-air continuum Davidson et al, 2002;Denmead and Reicosky, 2003;Kutzbach et al, 2007), likely due to suppression of natural pressure fluctuations (Hutchinson and Livingston, 2001) and possible alterations in turbulence between measured intervals (Hutchinson et al, 1993). Therefore, the CO 2 fluxes determined using linear regression likely result in an underestimation of fluxes in a closed-chamber environment (Kutzbach et al, 2007).…”
Section: Co 2 Fluxmentioning
confidence: 99%
“…The NE ff was calculated using the exponential change in chamber headspace CO 2 concentration (Kutzbach et al, 2007) regressed with time, as a function of volume, pressure and air temperature inside the chamber, according to the ideal gas law. The exponential regression was applied following because covering the soil and vegetation can manipulate the sponta-neous CO 2 fluxes across the soil-vegetation-air continuum Davidson et al, 2002;Denmead and Reicosky, 2003;Kutzbach et al, 2007), likely due to suppression of natural pressure fluctuations (Hutchinson and Livingston, 2001) and possible alterations in turbulence between measured intervals (Hutchinson et al, 1993). Therefore, the CO 2 fluxes determined using linear regression likely result in an underestimation of fluxes in a closed-chamber environment (Kutzbach et al, 2007).…”
Section: Co 2 Fluxmentioning
confidence: 99%
“…All these changes can lead to biased measurements of net gas flux. The minimum collar insertion recommended by Rochette and Eriksen-Hamel (2008) is 5 cm and according to Hutchinson and Livingston (2001), the error due to lateral gas diffusion in the soil for a collar insertion of 5 cm and a deployment time of 80 min can be around 10%. During the season we took soil cores to determine wfps, and extractable NH 4 þ and NO 3 À contents as explained in section 3.2 below.…”
Section: Soil N 2 O and Ch 4 Emissionsmentioning
confidence: 99%
“…[72] Pressure differences within the chamber can also cause large errors in the efflux measurements. [38][39][40]71,73] An increase in the pressure inside a chamber has the effect of slowing CO 2 diffusion, which in turn lowers the measured efflux rate. In contrast, a reduction in pressure draws CO 2 from the soil and leads to an overestimation of the true rate.…”
Section: Openmentioning
confidence: 99%
“…In the field the true value is not known so that the best error estimates are derived from modelled data. Hutchinson and Livingston [39] predicted errors of between 1 and 5% in rate measurements in relation to chamber wall insertion depth (ranging between 0 and 46 cm) for a number of different deployment times and soil air-filled porosity values. They concluded that an insertion depth of 10 cm was completely inadequate for dry, porous or coarse-textured soils, and less than 5 cm was adequate for fine-textured, wet or compacted soil.…”
Section: Mixing Of Atmospheric Air In the Soil Surfacementioning
confidence: 99%